Enhancing MSMEs competitiveness and sustainability through understanding economic management, digital literacy, and technology adoption in the digital era - Anshar Daud; Muh Syulhasbiullah; Ridwan Ridwan; Harlindah Harniati Arfan (Universitas Ahmad Dahlan, 2025)
The low implementation of understanding economic management in the micro small medium enterprises has led to limitations in technology utilization, digital financial management, and data-driven marketing strategies. This study aims to analyse the influence of understanding economic management on the use of digital technology and its impact on micro small medium enterprises performance. The research approach used a mixed method with a sample of 229 micro small medium enterprises through stratified random sampling. Data were collected through surveys, observations, in-depth interviews with 30 business actors, and documentation. Analysis techniques included multiple linear regression and a mediation-moderation model. The results showed that all hypotheses were significant. The main findings indicate that understanding economic management has a positive effect on the use of digital technology, digital financial efficiency, and marketing strategies. The novelty of this study lies in the integration of the three theory acceptance model constructs, digital finance, and economic management in one model, capable of explaining technology adoption behaviour more holistically. In conclusion, the success of micro small medium enterprises digital transformation requires synergy between economic literacy, technological preparation, and institutional support.